Filodemo, Testimonianze su Socrate, edizione, traduzione e commento a cura di E. Acosta Méndez e A. Angeli, Napoli, Bibliopolis, 1992. ISBN 88-7088-275-6 (Minerva, 2019)
Review: Filodemo, Testimonianze su Socrate, edizione, traduzione e commento a cura di E. Acosta Méndez e A. Angeli, Napoli, Bibliopolis, 1992. ISBN 88-7088-275-6